5-Fluorouracil-loaded PLA/PLGA PEG–PPG–PEG polymeric nanoparticles: formulation, in vitro characterization and cell culture studies. (18th April 2013) - Öcal, Harika; Arıca-Yegin, Betül; Vural, İmran and Goracinova, Katerina and Çalış, Sema
Abstract: In this study, 5-FU, a potent anticancer drug, is planned to be delivered via a new and promising drug delivery system, nanoparticles formed with hydrophobic core polymer and triblock copolymers; Poly(DL-lactic acid), Poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) copolymer (PLA/PEG-PPG-PEG) and Poly(D, L-lactide–co-glycolide)/Poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) copolymer (PLGA/PEG-PPG-PEG) nanoparticles. Particle size range of nanoparticles was found to be between 145 and 198 nm, which would promote the passive targeting of the nanoparticles to tumor cells based on the enhanced permeability and retention (EPR) effect. SEM images revealed all nanoparticles formulations to be spherical and without pores. Zeta potential, yield value and encapsulation efficiencies of 5-FU-loaded nanoparticles were within the range of −11.1 and −13.7 mV, 72.7–87.7% and 83.6–93.9%, respectively. Cumulative release of 5-FU was observed between 90% and 94.4% in all nanoparticle formulations by the end of 72 h, and fitness of release profiles to Higuchi model indicated matrix-controlled diffusion of the 5-FU from polymeric nanoparticles. Cell viability values of the cells treated with 5-FU-loaded nanoparticles were obtained as low as 47% and 52% with tetrazolium dye assay, suggesting that delivery of 5-FU via amphiphilic triblock copolymer nanoparticles would be a promising delivery system because of the EPR effect.